Higher visual art education objectives and teaching patterns to reach them - Antonina Korepanova; Kai Pata (Interaction Design and Architecture(s))
Visual art education has moved from the traditional studio model towards e-learning practices. This paper presents a comparative exploration of art education goals in research papers (N=48) and among visual art teachers in higher education (N=24), as well as the teaching patterns they use in online practice. We qualitatively analyzed research papers on art teaching goals and interviewed international higher-level visual arts art educators from different countries. The inductive analysis identified many visual art teaching goals and art teaching patterns the teachers used to reach their objectives in e-learning. The analysis connected the overarching learning objectives and art teaching patterns. The paper proposes a visualized model of art education objectives and patterns for art teaching in e-learning. By unveiling and categorizing art education patterns in e-learning mode, this research contributes to a deeper understanding of the relationship between pedagogical strategies and the overarching goals of art education.